Childhood Trauma is Associated with Altered Cortical Arousal: Insights from an EEG Study - Howells, Fleur M.; Stein, Dan J.; Russell, Vivienne A. (Frontiers in Integrative Neuroscience, 2012)
Background: Childhood trauma is associated with psychiatric disorders, yet the underlying psychobiological mechanisms that account for this link are not well understood. Alterations in cortical arousal may, however, play a key role in mediating this association. We hypothesised that childhood trauma would be associated with alterations in arousal during a task that required sustained attention and behavioural inhibition. Methods: Fifty-three healthy adults completed the Childhood Trauma Questionnaire which assesses physical neglect, emotional neglect, emotional abuse, physical abuse, sexual abuse, and denial of childhood trauma. These individuals underwent cortical (electroencephalography, EEG) and peripheral (heart rate, skin conductance responses, salivary cortisol) physiological recordings at rest (eyes open and eyes closed) and during performance of a visual go/no-go (GNG) task. Associations between reported childhood trauma and physiological measures were determined. Results: Physical and emotional neglect were correlated with decreased left parietal tonic α band power during resting conditions and during the GNG task. Emotional abuse was correlated with decreased right frontal α band power during rest, increased θ band power during the GNG task and cortisol at the end of the testing session. Physical and sexual abuse was correlated with delayed P300 latency and enhanced P300 amplitude during the no-go conditions of the GNG task. The denial scale was correlated with a decrease in θ and increase in α band power during the no-go conditions of the GNG task. Conclusions: The present study provides evidence that childhood trauma is associated with altered cortical arousal and that the pattern of this association is dependent on the form of childhood trauma experienced.